Neural Network on Stock Prediction using the Stock Prices Feature and Indonesian Financial News Titles - Nur Ghaniaviyanto Ramadhan; Imelda Atastina (International Journal on Information and Communication Technology (IJoICT), 2021)
Stocks are the most popular investments among entrepreneurs or other investors. When investing in stocks these investors tend to learn how to invest stocks correctly and when is the right time. For the problem of how to invest shares correctly can be used a variety of basic theories that already exist, but for the problem when the right time needs further learning. In this paper will purpose about stock price prediction using stock data indicators and financial headline data in Bahasa Indonesia. The machine learning model used is a multi-layer perceptron neural network (MLP-NN) with the highest accuracy produced by 80%.